Challenge Of Developing And Implementing Interactive Multimedia Courseware From 2D Animation To 3D Animation - Xuan, Liu (2009)
This research is done to find the challenges of developing and implementing interactive multimedia courseware from 2D animation to 3D animation. To find these challenges basically this research tries to explore and implement courseware in 3D interactive animation. The analysis focuses on differentiating the process of 2D animation and 3D animation using in interactive courseware, and the difficulties in building 3D interactive animation in courseware.